Emotion marketing : - Robinette, Scott (McGraw-Hill, 2001)
This book provides business readers with their first in-depth analysis of Hallmark's uncanny ability to forge lasting emotional bonds with a huge and devoted customer base that spans generations. More importantly, it describes original Emotion Marketing principles and techniques that you can put to work in you company.